Highly efficient (R-X-R)-type carbamates as molecular transporters for cellular delivery - Patil, Kiran M.; Naik, Rangeetha J.; Rajpal; Fernandes, Moneesha; Ganguli, Munia; Kumar, Vaijayanti A. (Journal of the American Chemical Society, 2012)
The (R-X-R) motif-containing arginine-rich peptides are among the most effective cell-penetrating peptides. The replacement of amide linkages in the (R-X-R) motif by carbamate linkages as in (r-ahx-r)(4) or (r-ahx-r-r-apr-r)(2) increases the efficacy of such oligomers several-fold. Internalization of these oligomers in mammalian cell lines occurs by an energy-independent process. These oligomers show efficient delivery of biologically active plasmid DNA into CHO-K1 cells.

Second generation, arginine-rich (R-X `-R)(4)-type cell-penetrating alpha-omega-alpha-peptides with constrained, chiral omega-amino acids (X `) for enhanced cargo delivery into cells - Patil, Kiran M.; Naik, Rangeetha J.; Vij, Manika; Yadav, Amit K.; Kumar, Vaijayanti A.; Ganguli, Munia; Fernandes, Moneesha (Bioorganic & Medicinal Chemistry Letters, 2014)
The syntheses of novel N-aminoalkyl proline-derived spacers (X') in polycationic (R-X'-R)-motif cell-penetrating alpha-omega-alpha-peptides are described as improved molecular transporters and their structural features studied by CD. FACS analysis shows enhanced cellular uptake and confocal microscopy indicates predominantly cytoplasmic localization. The oligomers are efficient at transporting pDNA into cells. The chirality together with the hydrophobicity and flexibility derived from the spacer chain are found to have marked influence on the cell-penetrating and cargo delivery properties of the cell-penetrating peptides (CPPs). The peptides containing N-(3-aminopropyl)-D-proline spacers are found to be the best at cell penetration and cargo delivery in the present study. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: (R-X-R)-motif; alpha-omega-alpha-Peptide; Cell-penetrating peptide; Constrained chiral amino acid; Peptidomimetics

RXR-carbamate - a novel molecular transporter for skin - Natarajan, Poornemaa; Patil, Kiran M.; Vij, Manika; Yadav, Amit K.; Kumar, Vaijayanti A.; Ganguli, Munia; Fernandes, Moneesha (Molecular Therapy, 2015)
18th Annual Meeting of the American-Society-of-Gene-and-Cell-Therapy (ASGCT), New Orleans, LA, MAY 13-16, 2015

Efficient cellular entry of (r-x-r)-type carbamate-plasmid DNA complexes and its implication for noninvasive topical DNA delivery to skin - Vij, Manika; Natarajan, Poornemaa; Yadav, Amit K.; Patil, Kiran M.; Pandey, Tanuja; Gupta, Nidhi; Santhiya, Deenan; Kumar, Vaijayanti A.; Fernandes, Moneesha; Ganguli, Munia (Molecular Pharmaceutics, 2016)
Arginine-rich cell penetrating peptides are powerful tools for in vitro as well as in vivo delivery of a wide plethora of biomolecules. However, presence of consecutive arginine residues leads to enhanced amenability for proteolytic degradation as well as steric hindrances for membrane interactions which compromise its bioavailability. In order to overcome these limitations we previously reported a safe and stable octaarginine based oligomer, i.e., (r-x-r)4-carbamate, where the backbone amide linkages were replaced by carbamate linkages and 6-aminohexanoic acid based spacer moieties were incorporated for better flexibility, hydrophobicity, optimal spacing of guanidinium groups, and protection against proteolytic cleavage; resulting in improved transfection efficiency over its amide counterpart. In the present work we have investigated the mechanism behind this enhanced transfection efficiency and, based on our observations, demonstrate how the synergistic effect of rationalized oligomer designing, complex characteristics, and cell type contributes to overall effective intracellular delivery. Our results indicate that the (r-x-r)4-carbamate plasmid DNA complexes primarily utilize lipid raft dependent pathway of cellular entry more than other pathways, and this possibly facilitates their increased entry in the lipid raft rich milieu of skin cells. We also emphasize the utility of oligomer (r-x-r)4-carbamate as an efficient carrier for topical delivery of nucleic acids in skin tissue. This carrier can be utilized for safe, efficient, and noninvasive delivery of therapeutically relevant macromolecular hydrophilic cargo like nucleic acids to skin.
Keywords: Cell penetrating peptides; endocytosis; nucleic acid delivery; skin penetration; transfection

Dendrimeric amide- and carbamate-linked lysine-based efficient molecular transporters - Yadav, Amit Kumar; Dey, Namit; Chattopadhyay, Sabyasachi; Ganguli, Munia; Fernandes, Moneesha (Organic & Biomolecular Chemistry, 2017)
Amide- and carbamate-linked dendrimeric oligomers are reported as molecular transporters. They effectively complex with pDNA and transport it into cells at an efficiency superior to Lipofectamine, when complexation is carried out by incubation overnight. The carbamate-linked K2C is superior to amide-linked K2A; their pDNA complexes have very low associated cytotoxicity.